The Role of Health Workers in Interprofessional Collaboration for Cancer Patient Navigators: A Scoping Review - Agung Subakti Nuzulullail; Aulia Diah Rahayu; Rurry Nindya Taluphyta; Ika Arif Lidiyana; Mohamad Rusdiansyah; Petrus Paris Rumsori; Riyati Riyati; Suci Wahyu Hariyanto; Wa Ode Umi Kalsum; Sri Hartini (Jurnal Keperawatan Indonesia, 2026)
Cancer remains a leading cause of death worldwide. The complexity of cancer care demands strong interprofessional collaboration (IPC), particularly within cancer patient navigator (CPN) programmes. However, research examining IPC in the context of CPN implementation is still limited. This scoping review aims to explore the various roles of healthcare workers in the IPC process within cancer navigator programme interventions. The review was conducted using four databases: PubMed, Clinical Key, EBSCOhost, and ScienceDirect. The Arksey and O'Malley framework was used to address the research question: “What is the role of health workers in interprofessional collaboration within cancer patient navigation?” Study selection followed the PRISMA-ScR 2020 guidelines, using the following criteria: Population (P): health workers; Concept (C): interprofessional collaboration; and Context (C): hospital and community settings. The inclusion criteria consisted of original articles published between 2019 and 2024, written in English, and discussing interprofessional collaboration in cancer navigation. Review articles, protocols, pilot studies, editorials, and books were excluded from the study. Quality assessment was conducted using the JBI Critical Appraisal tool. Out of 1,150 articles, 13 met the inclusion criteria. The identified roles of health workers included communicator, care provider, care coordinator, service provider, educator, documenter, emotional support provider, and facilitator. These roles appear across the early detection, diagnosis, treatment, and survivorship phases. IPC also has a distinct function within CPN and plays a critical role throughout all phases of cancer care. Future researchers are encouraged to identify barriers to IPC within CPN to support more effective implementation.